Embracing a Trauma-Sensitive Approach: One School’s Transformative Experience of Creating Equitable Schooling - Ballin, Amy (Journal of Teaching and Learning, 2023)
One pathway to creating more equitable schooling is through schools becoming trauma sensitive. Students exposed to trauma are more likely to struggle in school compared to their non-trauma-exposed peers. Changing the school environment allows trauma-exposed students more opportunities to access academics. This qualitative study explores the practices and strategies employed by one elementary school (K–5) to become trauma sensitive. Based on the data, five subthemes emerged that coalesce around the overarching theme of creating a caring community to achieve a trauma-sensitive school. For the purposes of this study, a caring community is defined as a group of people sharing a common workplace who have a true interest in the well-being of others in the community. The five subthemes include (1) the faculty’s commitment to creating a safe school, (2) intentional school design to foster support (covered in Ballin, 2022), (3) a commitment to engaging families, (4) a desire to make school fun, and (5) the principal’s support of the school community. By embracing practices aligned with trauma-sensitive schooling, this small school changed the learning environment to give more children chances for success despite current and past traumatic experiences.